A spatially explicit approach to prioritize protection areas for endangered freshwater mussels. Issue 1 (17th December 2018) - Dobler, Andreas H.; Geist, Juergen; Stoeckl, Katharina; Inoue, Kentaro
Abstract: In spite of their conservation importance, only a fraction of lakes and streams globally – including their catchments – are currently covered by conservation areas. To identify conservation gaps, assessing the spatial distribution of biodiversity in relation to conservation areas is a promising approach. A gap‐analysis approach was used to evaluate the protection status of the habitats of two endangered freshwater mussel species, Margaritifera margaritifera (Linnaeus, 1758) and Unio crassus (Philipsson, 1788), in the Federal State of Bavaria, Germany. First, ecological niche models (ENMs) were developed for both mussel species based on presence‐only data in order to identify suitable habitats. Second, binary maps of suitable and unsuitable habitats for the species were used to compare different categories of currently protected areas in a gap analysis. The ENMs for M. margaritifera revealed a spatially restricted distribution with good model performance, whereas the spatial distribution of U. crassus was wider and the model performance was weaker. For M. margaritifera, a higher percentage of suitable habitat is already under some sort of protection, whereas for U. crassus only half of the suitable habitats are under protection. The results suggest that suitable habitats of both species are not sufficiently protected. More effective conservation of M. margaritifera and U. crassus requires separate management: increasing the respective protection categories of already protected habitats of M. margaritifera and incorporating an increased area of suitable habitats under legal protection for U. crassus .